2021
DOI: 10.21093/ijeltal.v6i1.849
|View full text |Cite
|
Sign up to set email alerts
|

Community of Inquiry for Students’ Autonomy in English Language Learning: A Case of Philippines High School

Abstract: There were many researchers bring out the topic of the community of inquiry (CoI) in education but there were still few teachers who were aware of the importance of CoI and how to implement CoI into learning. This study was, then, aimed at finding out (1) how the community of inquiry was explicitly applied to English language learning, as well as (2) the impact of the community of inquiry to promote students’ autonomous learning. This research was a case study. The researcher used observation and interview as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These insights point to the necessity of well-designed e-learning platforms. Extending this understanding, research by Hilliard et al (2019) and Akay (2021), along with Rachman et al (2021), demonstrates the CoI framework's effectiveness in diverse English learning contexts. Hilliard et al and Akay focused on online environments, while Rachman et al showed its utility in enhancing autonomy and intelligence through group activities in a Philippine high school.…”
Section: The Community Of Inquiry (Coi) Frameworkmentioning
confidence: 82%
“…These insights point to the necessity of well-designed e-learning platforms. Extending this understanding, research by Hilliard et al (2019) and Akay (2021), along with Rachman et al (2021), demonstrates the CoI framework's effectiveness in diverse English learning contexts. Hilliard et al and Akay focused on online environments, while Rachman et al showed its utility in enhancing autonomy and intelligence through group activities in a Philippine high school.…”
Section: The Community Of Inquiry (Coi) Frameworkmentioning
confidence: 82%
“…It is important that their students be involved in creating and innovating with the help of digital technology to achieve learning goals (Permono et al, 2019). The improvement of the teaching and learning process is enabled by instructors' ICT self-efficacy (Rachman et al, 2021). ICT self-efficacy should focus on reorganizing the educational process and rethinking how students learn rather than just on specific ICT skills (Kaminskienė et al, 2022).…”
Section: : I Am Ready and Happy To Adapt Technology 20: We Must Be Re...mentioning
confidence: 99%
“…For distant education, the community of inquiry or CoI framework [5]- [12] is used in many of ways [5]- [12]. These studies show that the framework's use in teaching English as foreign language (TEFL) has produced beneficial effects for teachers and students alike.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the adoption of CoI in TEFL have thus far been confined to higher education institutions and rarely reported on in secondary schools. Research conducted in high schools indicated a strong association between the deployment of CoI and the increase of English language competency [12]. Using the CoI framework to teach four English language skills in secondary education is achievable because of this feature.…”
Section: Introductionmentioning
confidence: 99%